Relationships between rating of perceived exertion and blood indices during training sessions of various intensity in female taekwondo players - Obminski, Z.; Zdanowicz, R.; Gradzka, E. (Journal of Combat Sports and Martial Arts, 2013)
This study aimed to verify hypothesis whether responses of selected blood indices and perception of effort are related to intensity of training sessions in exercising female taekwondo players. Material and methods. Seventeen senior female taekwondo players were subjected to the study. They underwent two various training sessions lasting 1.5h, defined as less intensive training (LIT), and as more intensive one (MIT).The both exertions were performed on the two separated days in a randomized order in the afternoon. Capillary blood was drown from earlobe prior to the training session and within 3 minutes after its completion for determination of serum hormones (cortisol, testosterone and dihydroepiandrosterone sulfate). Blood lactate were determined after the most three vigorous exercises performed during each training. Post-training fatigue expressed as rating perceived exertion (RPE) were estimated using visual analogue scale. Results. Plasma androgens levels increased significantly only after more intensive training. This magnitude of this rise was less after adjusted data to the initial plasma volume. More intensive effort brought about rise of C level and total amount of C in circulation and higher RPE than those after less intensive one. Blood lactate concentration was higher during more intensive training at three time points. Changes of tested blood parameters and RPE correlated significantly. Conclusions. More intensive exercise performed during training session brought about clearer hormonal and metabolic responses. Moreover, post-training directions of the changes in blood indices and RPE changes were nearly parallel.